The Impact of Coffee Farmer Certification on Farming Sustainability (Bibliometric and Content Analysis) - Putra Irwandi; M. Fariz Afif Hasibuan; Hendris Syah Putra; Mika Bintang Rivaldo M Sihotang (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Coffee farmer certification serves as a strategic tool in promoting sustainable agricultural practices, but implementation remains low at the farmer level. This study aims to fill this gap by conducting a comprehensive review of the relevant literature through a bibliometric and content analysis approach to identify research trends, major publishing countries, key affiliations, main themes, and the direction of coffee certification development and its impact on agricultural sustainability in various economic, social, and environmental dimensions. This study uses the Scopus database, with an initial dataset of 206 articles published over 10 years (2015–2025). After applying inclusion criteria covering economics, management, and business; English-language articles; duplicate removal; and topic relevance, 63 articles were selected for final analysis. The data were analyzed using PRISMA diagrams, R-Studio software, and VOSviewer. Results showed that publications on coffee certification have increased at an average annual growth rate of 2.81%, with World Development and Ecological Economics as the most productive journals. Germany, the United States, and the Netherlands emerged as the leading contributors. The most frequently used keywords were certification, coffee, smallholders, and sustainability. Content identification results showed that certification positively affects economic, social, and environmental dimensions. The scientific contribution to farmers is that implementing certification will increase the selling value of coffee, thereby increasing income, consumer confidence, strengthening cooperatives and farmer solidarity, and providing wider access to markets for adopting sustainable agriculture. This study also enriches the literature on the impact of coffee certification on sustainability, providing policymakers with insights to improve institutional support and regulatory frameworks for farmer-level coffee certification, such as training and financial capital.